Automated Clinical Grade Expansion of Regulatory T Cells in a Fully Closed System - Marín Morales, José Manuel; Münch, Nadine; Peter, Katja; Freund, Daniel; Oelschlägel, Uta; Hölig, Kristina; Böhm, Thea; Flach, Anne-Christine; Keßler, Jörg; Bonifacio, Ezio; Bornhäuser, Martin; Fuchs, Anke (Frontiers in Immunology, 2019)
Adoptive transfer of T regulatory cells (Treg) has been successfully exploited in the context of graft-versus-host disease, transplantation and autoimmune disease. For the majority of applications, clinical administration of Treg requires laborious ex vivo expansion and typically involves open handling for culture feeds and repetitive sampling. Here we show results from our approach to translate manual Treg manufacturing to the fully closed automated CliniMACS Prodigy® system reducing contamination risk, hands-on time and quality variation from human intervention. Polyclonal Treg were isolated from total nucleated cells obtained through leukapheresis of healthy donors by CD8+ cell depletion and subsequent CD25high enrichment. Treg were expanded with the CliniMACS Prodigy® device using clinical grade cell culture medium, rapamycin, IL-2 and αCD3/αCD28 beads for 13-14 days. We successfully integrated expansion bead removal and final formulation into the automated procedure, finalizing the process with a ready to use product for bedside transfusion. Automated Treg expansion was conducted in parallel to an established manual manufacturing process using G-Rex cell culture flasks. We could prove similar expansion kinetics leading to a cell yield of up to 2.12x109 cells with the CliniMACS Prodigy® and comparable product phenotype of >90% CD4+CD25highCD127lowFOXP3+ cells that had similar in vitro immunosuppressive function. Efficiency of expansion bead depletion was comparable to the CliniMACS® Plus system and the final ready-to-infuse product had phenotype stability and high vitality after overnight storage. We anticipate this newly developed closed system expansion approach to be a starting point for the development of enhanced throughput clinical scale Treg manufacture, and for safe automated generation of antigen-specific Treg grafted with a chimeric antigen receptor (CAR Treg).